UWB radar multipath propagation effects - Čermák, Dušan (Univerzita Pardubice, 2006)
The paper is dealing with the UWB technology in the radar technique and communications. Special attention is given to the multipath effects in the time domain signal representation, which should be considered for the UWB systems. This is the case when both direct and (multiply) reflected signals are received. The reflections are due to ground, wall and nearby objects. A program was created to model this multipath propagation. The inverse Fourier transform (IFFT) to analyze the signal responses in the time domain was also used and the delay between direct and reflected signals was shown. It is concluded that multiple reflections and multipath effects are much smaller for UWB signals than for CW narrow-band applications as interference minima and maxima do not occur for the same frequencies.
Mnohocestné šíření radiových vln v technice UWB radarů
Keywords: UWB technika; radarová oblast; komunikační oblast; mnohocestné šíření radiových vln